Strategi Pengembangan Asuransi Jiwa - Sulastri Sulastri; Amzul Rifin; Bunasor Sanim (Jurnal Aplikasi Bisnis dan Manajemen (JABM), 2018)
Insurance is a financial institution that is engaged in the service field and a Non-Bank Financial Institution. The achievement of PT Asuransi Jiwa TASPEN is not maximal, due to the limitations of facilities, infrastructure, and human resources in the development of the market, but the opportunities of this company in achieving the targets set will be very large if it implements strategies that fit the factors it experiences. This study aims to identify and study the internal and external factors that affect the existence of PT Asuransi Jiwa TASPEN and to formulate appropriate strategic alternatives to be applied in this company. These internal and external factors strongly influence the company. With its strengths, weaknesses, opportunities and threats, the management must utilize SO strategy that harnesses its largest power to take advantage of opportunities. The SO alternative strategies include the strengthening of the partnerships with the government and availability of insurance programs to the needs of civil servants, development of marketing distribution, opening of the office channeling at the branch offices in order to anticipate market development, and improvement of the quality and quantity of human resources.Keywords: alternative strategies, insurance, Asuransi Jiwa, SWOT